Documental salas de emergencia - Yépez Liut, Evelyn Jacqueline (2011)
This documentary project about the emergency rooms in Quito city has been filmed in Hospital Carlos Andrade Marín and Eugenio Espejo Hospital. It shows the events that take place here and the atmosphere inside an emergency room. The documentary highlights the work of the health professionals in our country, their capacities and the knowledge they posses. The documentary shows the viewer how life is like inside the emergency room of a teaching hospital, the working conditions and the complex and difficult situations that the hospital’s crew has to deal with in day to day bases. This documentary gathers testimonies and experiences of doctors, residents and nurses along with images of patients while they are being treated, which is used as this story’s conductor.